Collateral Booms and Information Depletion - Asriyan, Vladimir; Laeven, Luc; Martín, Alberto (Review of Economic Studies, 2022)
Abstract We develop a new theory of information production during credit booms. Entrepreneurs need credit to undertake investment projects, some of which enable them to divert resources. Lenders can protect themselves from such diversion in two ways: collateralization, and costly screening that generates durable information about projects. In equilibrium, the collateralization-screening mix depends on the value of aggregate collateral. High collateral values make it possible to reallocate resources towards productive projects, but they also crowd out screening. This has important dynamic implications. During credit booms driven by high collateral values (e.g. real estate booms), economic activity expands but the economy’s stock of information on existing projects gets depleted. As a result, collateral-driven booms end in deep crises and slow recoveries: when booms end, investment is constrained both by the lack of collateral and by the lack of information on existing projects, which takes time to rebuild. We provide empirical support for the mechanism using US firm-level data.